Effect of fertilizer and plant-density management on productivity and economics of maize (Zea mays) + blackgram (Phaseolus mungo) intercropping - Singh, M K; Pashupalak, S; Pal, S K; Thakur, R; Verma, U N (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during rainy seson of 1988 and 1989 on sandy-loam soil to study the effect of fertilizer andplant population of black gram of productivity of maize (Zea mays L.) + blackgram (Phaseolus mungo L.) intercropping.Separate fertilization (fertilizer for component crops applied seprately to respective rows) gave 8.4% higher grain yield ofmaize than uniform fertilization (fertilizer for component crops mixed together and applied uniformly in rows irrespective ofcrops). Reduction in population of blackgram as Intercrop below 100% decreased the productivity of the system. Grain yield ofinter cropped maize was almost similar(4.04-4.18 tonnes/ha) to its sole crop (4.32 tonnes/ha) when grown with 100% population(20 kg seed/ha) and 50 (10 kg N and 8.8 kg P/ha) to 100% (20 kg N and 17.6 kg P/ha) fertilizer to blackgram and componentcrops fertilized separately. This combination also gave higher grain yield (0.82-0.84 tonnes/ha) of the intercrop blackgram,suggesting that 50% fertilizer to blackgram could be saved without any significant reduction in production polential of thesystem. Maize + blackgram intercropping system with 100% population and 50% fertilizer to blackgram and fertilized separatelyto both the component crops gave maize-equivalent yield of 5.88 tonnes/ha and net rturns of Rs 10470/ha.